Profile of Patients Attending as Psychiatric Emergency at General Hospital - Tulachan, P; Chapagain, M; Ojha, S P; Dhungana, S (Journal of Psychiatrists' Association of Nepal, 2015)
Introduction: Scaling of services in any area requires knowledge of the pattern of illnesses and their various presentations. We therefore conducted this study aiming to see the pattern of neuropsychiatric illness in an emergency department of tertiary care center.  Methods: A prospective study was carried out to assess the pattern of psychiatric morbidity as well as pattern of presenting symptoms in the general emergency room services. Total 340 patients were sought for psychiatric consultation over a period of one and half years from Emergency Room of Tribhuvan University Teaching hospital, Kathmandu.Results: Out of these patients, 281 patients (82.7%) were found to have diagnosable psychiatric disorder. Most of the patients were in the age group of 31-40 years (25.6%), and from valley itself (56.2%).Males (55.9%) outnumbered females. Most common presenting symptoms were disturbed behavior and intentional self harm. Out of the patients who received the diagnosis of Category F- Mental and Behavioral disorders of the ICD-10 (82.7%), 26.8% were suffering from the Neurotic, stress-related and somatoform disorders and 26.5% were suffering from Mental and behavioral disorder due to psychoactive substance use. From the remaining 17.3% of patients, 14.1% of cases belonged to who attempted intentional self harm and rest were suffering from systemic disorder.Conclusion: Thus, this study emphasizes the importance of clinical and demographic characteristics of patients seeking psychiatric care in emergency service in order provide proper management.J Psychiatric Association of Nepal Vol .3, No.2, 2014, pp: 31-36DOI: http://dx.doi.org/10.3126/jpan.v3i2.12387